Nanoarchitectured CNTs-Grafted Graphene Foam with Hierarchical Pores as a Binder-Free Cathode for Lithium-Oxygen Batteries. Issue 9 (1st January 2018) - Wan, Weihua; Zhu, Xingbao; He, Xianglei; Wang, Yu; Yan, Yingzhang; Wu, Yuanguo; Lü, Zhe
Abstract : In this study, a three-dimensional CNTs-grafted graphene foam has been fabricated by a chemical vapor deposition method. The nanoarchitectured composite is employed as a cathode for lithium-oxygen (Li-O2 ) batteries and exhibits a substantially enhanced capacity of 20300 mAh g −1 at 0.05 mA cm −2, the number of which is among the highest prototype Li-O2 batteries reported to date. And the cathode can still exhibit a capacity of 3000 mAh g −1 when the current density is increased to 0.15 mA cm −2 . The improved performance, e.g., discharge capacity and rate capability, is mainly attributed to the synergistic effects of CNTs and graphene, which not only provide an effective channel for the transportation of oxygen and Li ion but also offer more and fast pathways for electron transport. In addition, the forest distribution of CNTs hinders the restack of graphene, contributing to the stability of Li-O2 batteries. This study demonstrated that the CNTs-grafted graphene foams would be likely to be a good alternative cathode material for Li-O2 batteries in the future.